Synthesis of ruthenium supported on protonated fibrous silica ZSM-5 for methanol to olefin reaction - Mohamad Afiq Hakimie Aziz, 1995-, author; Che Rozid Mamat, supervisor; Aishah Abd. Jalil, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018